The Effect of Using Virtual Reality in Urinary Catheter Insertion Procedures on Nursing Students’ Self-Efficacy - Dinda Ayu Apriliani; Iqbal Pramukti; Dyah Setyorini (Universitas Padjadjaran, 2023)
Self-efficacy is a person’s belief or confidence in doing something. Self-perception related to confidence in the learning process or learning strategy is often called “learning self-efficacy” where it reflects how confident a learner is in achieving certain learning objectives in the context of performing clinical skills of urinary catheterization. In developed countries, virtual reality is proven to be able to increase student self-efficacy but in developing countries there is still limited research. The purpose of this study was to see the effect of virtual reality learning media on the self-efficacy of nursing students in the learning process in Indonesia as a developing country. This research design is a quantitative study with a pre-experiment research design with one intervention group with a pre-test post-test design approach. The sampling technique used was purposive sampling with 49 nursing students of the Faculty of Nursing, Padjadjaran University as samples. The instrument used in this study was the Learning Self Efficacy Scale (L-SES) for Clinical Skills questionnaire consisting of 12 question items. Data analysis was carried out univariately and bivariately using the dependent t-test because the data were normally distributed. The results showed that there was a significant difference between the pre-test and post-test which showed an average increase of 13.65 points. The use of VR learning media in the act of urinary catheterization and static results show a value of p = 0.001 <0.05 it means significantly increase learning self-efficacy. So it can be concluded that virtual reality learning media in catheterization actions have an effect on increasing the self-efficacy of nursing students in Indonesia as a developing country.